2018
DOI: 10.1016/j.childyouth.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between child maltreatment and adolescent body mass index trajectories

Abstract: This study examines the relationship between childhood maltreatment experiences and body mass index (BMI) over time. Using data from the National Longitudinal Study of Adolescent to Adult Health, we use latent profile analysis to create child maltreatment experience classes and latent growth modeling to understand how classes relate to BMI trajectories from adolescence to early adulthood. The best-fitting model suggests four child maltreatment experience classes: 1) poly-maltreatment (n=607); 2) physical abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Previous research investigating the longitudinal relationship between child maltreatment and BMI has evaluated whether maltreatment alters an individual's BMI trajectory. 15,[19][20][21] However, prior studies have not considered how the association between maltreatment and BMI changes as individuals age. This study used data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) to test when the associations between types of child maltreatment (i.e., physical, sexual, and emotional abuse) and BMI are strongest between 13 to 28 years, and whether different patterns exist for males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research investigating the longitudinal relationship between child maltreatment and BMI has evaluated whether maltreatment alters an individual's BMI trajectory. 15,[19][20][21] However, prior studies have not considered how the association between maltreatment and BMI changes as individuals age. This study used data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) to test when the associations between types of child maltreatment (i.e., physical, sexual, and emotional abuse) and BMI are strongest between 13 to 28 years, and whether different patterns exist for males and females.…”
Section: Introductionmentioning
confidence: 99%
“…TVEM results of examining associations between maltreatment types and BMI over ages[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The solid black curves in the figure correspond to coefficient estimates of the association between maltreatment and BMI across time (i.e., age), and shaded regions correspond to the 95% confidence intervals of the coefficient estimates across time.…”
mentioning
confidence: 99%
“…As for the accumulation of ACEs, the significant association of two ACEs with overweight and obesity became nonsignificant after adjusting for maternal age, child's sex, grade, year conducted a survey, school, and parental obesity. Although some studies have found an association between the accumulation of ACEs and increased BMI in adolescents ( 12 , 13 , 19 ), other studies have shown no significant association between child abuse and increased BMI ( 36 , 37 ). Sokol et al ( 37 ) who examined the association between child abuse and BMI across adolescence found that adolescents who experienced abuse, who did not experience physical abuse, and who experienced both physical abuse and neglect all exhibited stable BMIs.…”
Section: Discussionmentioning
confidence: 94%
“…Although some studies have found an association between the accumulation of ACEs and increased BMI in adolescents ( 12 , 13 , 19 ), other studies have shown no significant association between child abuse and increased BMI ( 36 , 37 ). Sokol et al ( 37 ) who examined the association between child abuse and BMI across adolescence found that adolescents who experienced abuse, who did not experience physical abuse, and who experienced both physical abuse and neglect all exhibited stable BMIs. However, adolescents who experienced sexual abuse and co-occurring physical abuse and neglect showed a rapid increase in BMI.…”
Section: Discussionmentioning
confidence: 94%
“…The relation between childhood maltreatment and overweight has been confirmed by two meta-analyses including 190,285 and 112,708 participants, respectively (12,13). Longitudinal studies with several assessments have shown that maltreatment is related to accelerated weight gain (14)(15)(16)(17), but report conflicting results with regard to which type of maltreatment drives this effect.…”
Section: Introductionmentioning
confidence: 92%